Dampak Board Independence dan Digital Competence terhadap Kinerja Keuangan Melalui Board Diversity: Studi pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Nursafitri Ade Kamula; Chaerul Adhim; Asmawati Asmawati (AKUNTANSI 45, 2026)
This study aims to analyze the effect of Board independence and Digital Competence on financial performance, with Board Diversity as an intervening variable, in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2023-2025 period. This study uses a quantitative approach with explanatory research. The sampling technique used purposive sampling, resulting in 81 companies or 243 observational data over three years of the study. The data used are secondary data obtained from annual reports and company financial reports. Data analysis was performed using descriptive statistics, classical assumption tests, multiple linear regression analysis, and the Sobel test with the help of IBM SPSS software. The results of the study indicate that Board independence and Digital Competence do not significantly influence company financial performance. In addition, Board independence and Digital Competence also do not significantly influence Board Diversity. Meanwhile, Board Diversity has a positive and significant effect on company financial performance. The results of the mediation test indicate that Board Diversity is unable to mediate the influence of Board independence and Digital Competence on company financial performance. This study shows that Board Diversity is a factor that plays an important role in improving company financial performance, so companies need to strengthen the implementation of Board Diversity policies as part of their corporate governance strategy to face the challenges of digital transformation and increasingly complex industrial competition.